Endosymbiotic bacteria within the nematode-trapping fungus Arthrobotrys musiformis and their potential roles in nitrogen cycling - Zheng, Hua; Chen, Tong; Li, Wenjie; Hong, Jianan; Xu, Jianping; Yu, Zefen (Frontiers in Microbiology, 2024)
Endosymbiotic bacteria (ESB) have important effects on their hosts, contributing to its growth, reproduction and biological functions. Although the effects of exogenous bacteria on the trap formation of nematode-trapping fungi (NTF) have been revealed, the effects of ESB on NTF remain unknown. In this study, we investigated the species diversity of ESB in the NTF Arthrobotrys musiformis using high-throughput sequencing and culture-dependent approaches, and compared bacterial profiles to assess the effects of strain source and culture media on A. musiformis. PICRUSt2 and FAPROTAX were used to predict bacterial function. Our study revealed that bacterial communities in A. musiformis displayed high diversity and heterogeneity, with Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria as the dominant phyla. The ESB between A. musiformis groups isolated from different habitats and cultured in the same medium were more similar to each other than the other groups isolated from the same habitat but cultured in different media. Function analysis predicted a broad and diverse functional repertoire of ESB in A. musiformis, and unveiled that ESB have the potential to function in five modules of the nitrogen metabolism. We isolated nitrogen-fixing and denitrifying bacteria from the ESB and demonstrated their effects on trap formation of A. musiformis. Among seven bacteria that we tested, three bacterial species Bacillus licheniformis, Achromobacter xylosoxidans and Stenotrophomonas maltophilia were found to be efficient in inducing trap formation. In conclusion, this study revealed extensive ESB diversity within NTF and demonstrated that these bacteria likely play important roles in nitrogen cycling, including nematode trap formation.